Cultural capital and business success among entrepreneurs - Antonius Purwanto (Journal of Economics, Business, and Accountancy Ventura, 2016)
This article is about how the role of cultural capital in development of industrial cluster of ceramic art in Kasongan. This article based on research that make use of qualitative methods by interviewing informants such as entrepreneurs, craftsman, ceramic artist, government official, and technical staff of Technical Service Unit (TSU). The purpose of this article is to show how cultural capital plays role in business success among entrepreneurs and in struggling of the entrepreneurs to achieve high position in social-economic stratification. Empirical evidence show that entrepreneurs with a lot of cultural capital produce ceramic designs that more artistic, creative and innovative than those who with a little of cultural capital. Besides, cultural capital also supports meaningful interaction between entrepreneurs and buyers with various social-cultural backgrounds. The design that are innovative, creative and artistic and the meaningful interaction make ceramic product of entrepreneurs more easily to be purchased by buyers. As consequence, entrepreneurs with a lot of cultural capital more successful in their business and achieve high position in social-economic stratification.